Mixed bilayers of phosphatidylcholine with dialkylaminostyrylhetarene dyes for AChE-assisted fluorescent sensing of paraoxon - Elistratova, Julia G.; Akhmadeev, Bulat S.; Islamova, Liliya N.; Fazleeva, Guzel M.; Kalinin, Alexey A.; Orekhov, Anton S.; Petrov, Konstantin A.; Sinyashin, Oleg G.; Mustafina, Asiya R. (Journal of molecular liquids, 2022)
[Display omitted] •pH-sensitive fluorescence of dyes incorporated into phosphatidylcholine (PC)-based bilayers.•Dye’s structure optimization for sensitivity to the acidification arisen from AChE-catalyzed hydrolysis of ACh.•Monitoring of the hydrolysis process via dye-PC bilayers is affected by their interaction with AChE.•Dye-PC bilayers are sensitive to paraoxon-induced inhibition of AChE.•Lower detection limit of paraoxon by the dye-PC bilayers is 0.5 nM. The present work introduces the pH-sensitive fluorescence of the series of dialkylaminostyrylhetarene dyes incorporated into phosphatidylcholine (PC)-based bilayers as the basis for sensing of an increased acidity produced by the hydrolysis of acetylcholine (ACh) catalyzed by acetylcholinesterase (AChE). The pH-sensitivity of the dye-PC bilayers is optimized by the variation of the dye structure. However, the ability of dye-PC bilayers to sense the start of the hydrolysis when pH is within 8.0–7.0 disagrees with their pH-sensitive fluorescence detectable at pH below 6.0. This indicates that the proximity of the dyes to the enzyme results in the more acidic microenvironment of the dye than the acidity in the bulk of the solution. The time resolved fluorescent response of the dye-PC bilayers to the AChE-catalyzed hydrolysis indicates that the sensitivity of the dye-PC bilayers to the hydrolysis process is the greatest within the first few minutes, while the further decrease in the sensitivity derives from both diffusion process and aggregation of dye-PC bilayers derived from their protonation in the acidic microenvironment. This highlights the interaction of the dye-PC bilayers with AChE as the main reason for their ability to the sense the hydrolysis of ACh. The inhibition of AChE by pollutant paraoxon can be determined with the lower detection limit at 0.5 nM under the short incubation time equal to ten minutes.